2015
DOI: 10.4103/0253-7613.169585
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of rheumatoid arthritis following adjunct statin therapy

Abstract: Objective:Rheumatoid arthritis (RA) is characterized by symmetric peripheral polyarthritis, inflammatory synovitis, and articular destruction. Statins, 3-hydroxy-3-methylglutaryl coenzyme A-reductase inhibitors, mediate significant vascular risk reduction in patients with coronary artery disease by promoting reduction in plasma levels of low-density-lipoprotein cholesterol. Extensive in vitro data, experimental studies and more recently few clinical trials have strongly suggested statins to possess an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
0
16
0
2
Order By: Relevance
“…In the trial of atorvastatin in RA (a 6-month period, placebo-controlled, and randomized clinical trial with atorvastatin), the additional treatment with atorvastatin was suggested to reduce RA activity (p=0.004), swollen joint scores (p=0.006), and serum C-reactive protein levels (p<0.001; McCarey et al, 2004). Moreover, other reports also supported the opposite correlation between statin use and RA risk (Chodick et al, 2010;Das et al, 2015). However, there is a report demonstrating that statin has no apparent effect on RA activity (Akiyama et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the trial of atorvastatin in RA (a 6-month period, placebo-controlled, and randomized clinical trial with atorvastatin), the additional treatment with atorvastatin was suggested to reduce RA activity (p=0.004), swollen joint scores (p=0.006), and serum C-reactive protein levels (p<0.001; McCarey et al, 2004). Moreover, other reports also supported the opposite correlation between statin use and RA risk (Chodick et al, 2010;Das et al, 2015). However, there is a report demonstrating that statin has no apparent effect on RA activity (Akiyama et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, expectedly, statins can also mediate cholesterol-unrelated effects, such as anti-inflammatory, antiproliferative, antioxidant, immunomodulatory, and antithrombotic effects (DuBroff and de Lorgeril, 2015) without immunosuppression. In addition, some cohort studies have suggested the benefits of statin use in RA patients (Chodick et al, 2010;Das et al, 2015;McCarey et al, 2004). However, it remains to be revealed how statins affect the pathogenesis of RA.…”
Section: Introductionmentioning
confidence: 99%
“…Statin supplement is expected to be beneficial in RA. It reduces the production of inflammatory molecules and disrupts the oxidative stress/inflammation cycle [35]. Tetrahydrobiopterin (BH4) is a cofactor of nitric oxide synthase.…”
Section: Medication Effectsmentioning
confidence: 99%
“…При симптоматических заболеваниях перикарда глюкокортикоиды (ГК) и нестероидные проти-вовоспалительные препараты (НПВП) вызывают быстрое улучшение [35]. Имеются указания, что статины, благода-ря своему плейоторопному действию на воспалительные и иммунные медиаторы, могут не только улучшать тече-ние РА, но и уменьшать кардиологические и сосудистые ВП [36]. Эпидемиологические исследования обнаружили, что сердечно-сосудистая смертность высока у больных ранним и развернутым РА и неожиданно выше у женщин, традиционно имеющих низкий риск сердечно-сосудистой смертности [33,37].…”
Section: клинико-диагностический анализ внесуставных проявленийunclassified